SOCIO-HISTORICAL PRECONDITIONS FOR THE FORMATION OF YOUTH CULTURE IN 20TH CENTURY AMERICAN SOCIETY (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the socio-historical conditions that shaped the emergence of youth culture and the social construction of adolescence in the United States from the late nineteenth to the late twentieth century. Drawing on historical, sociological, and postmodern perspectives, the study demonstrates that adolescence is neither a universal nor biologically fixed life stage, but rather a product of industrialization, urbanization, educational expansion, economic restructuring, and state regulation. The article traces how schooling, labor laws, mass media, consumer culture, and political movements contributed to the institutionalization of adolescence and the rise of a distinct youth identity characterized by autonomy, rebellion, and peer-based socialization. Particular attention is paid to class, race, gender, and power relations, highlighting how adolescent experiences have been uneven and deeply shaped by social inequality. By integrating poststructuralist critiques, the article challenges developmental models of adolescence and argues for an interdisciplinary understanding of youth as a historically contingent and politically regulated social category.